Projection of land use change in Otavalo- Ecuador: a vision to year 2031 - Galiano Suárez, Mariana Alejandra; Suárez Salazar, Jonathan Daniel; Rosales Enríquez, Oscar Armando; Jácome Aguirre, Gabriel Alexis; Arias Muñoz, Darío Paúl (SATHIRI, 2024)
Land use change originates in anthropogenic activities and causes loss of ecosystems. In this study, land use in the canton of Otavalo was projected based on the analysis of land use change between 1993 and 2012. For this purpose, aerial photographs from 1993, 2002, and 2012 were used to perform a supervised classification using the maximum likelihood method, obtaining maps of land cover and land use. The Kappa index was applied for the classification validation, and a value of 0.93 was obtained. As a result of the classification, 12 categories of land cover and land use were obtained, showing that between 1993-2012, there was a 2% loss in native forest and paramo, and a 69% increase in bare soil, 16% in planted forest and 15% in agricultural and livestock mosaic. In the future projection to 2031, these transitions are expected to continue and even deepen since the paramo and native forest will continue to decrease, and the agricultural and livestock mosaic, together with crops, planted forest, and areas without vegetation, will continue to increase. This changing trend implies sustained agricultural and livestock frontier growth, urban expansion, and the reduction of fragile ecosystems.